From Gutenberg to the Internet: A Sourcebook on the History of Information Technology. - D. Lynn Koenig (Issues in Science and Technology Librarianship)
The article reviews the book "From Gutenberg to the Internet: A Sourcebook on the History of Information Technology," by Jeremy M. Norman.